2016
DOI: 10.1177/0265407516670533
|View full text |Cite
|
Sign up to set email alerts
|

Computer-mediated communication (CMC) and social support

Abstract: Despite the growth in research examining the use of computer-mediated communication (CMC) for exchanging social support, there remains much to learn about the support-related implications of CMC. An experiment was conducted to examine the influence of the reduced social cues associated with CMC on the outcomes of supportive interaction. Participants discussed a stressor with a confederate either face-to-face or via CMC and received informational or emotional support. Although they received the exact same suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 50 publications
(101 reference statements)
0
24
0
Order By: Relevance
“…Furthermore, adolescents who used high levels of online emotional support seeking were found to experience increases in worry, jealousy, and loneliness (Duvenage et al, 2020). Similarly, Rains et al (2017) found that college students who received support via IMing experienced higher levels of uncertainty and worry than those who received the same support in-person in an experimental study. Finally, in recent work by Vermeulen et al (2018a), Flemish adolescents identified that they preferred to share emotions face-to-face rather than online.…”
Section: Potential Limitations For Adolescent Girls Seeking Support Umentioning
confidence: 90%
See 2 more Smart Citations
“…Furthermore, adolescents who used high levels of online emotional support seeking were found to experience increases in worry, jealousy, and loneliness (Duvenage et al, 2020). Similarly, Rains et al (2017) found that college students who received support via IMing experienced higher levels of uncertainty and worry than those who received the same support in-person in an experimental study. Finally, in recent work by Vermeulen et al (2018a), Flemish adolescents identified that they preferred to share emotions face-to-face rather than online.…”
Section: Potential Limitations For Adolescent Girls Seeking Support Umentioning
confidence: 90%
“…Many adolescents report finding that self-disclosure is easier online than in face-to-face contexts (Schouten et al, 2007). This view is supported by the hyperpersonal communication model, in which reduced social cues in electronic exchanges stimulate self-disclosure through an 'online disinhibition effect' (Rains et al, 2017;Suler, 2004;Walther et al, 2015). Increased self-disclosure in turn predicts having higher quality friendships (Valkenburg & Peter, 2009).…”
Section: Why Might Adolescent Girls Use Digital Media To Seek Support?mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies investigating helper behaviour have developed a distinction between (1) behaviour focusing on problem solving and removal of stressors (problem-centred counsellor behaviour, PCCB) and (2) helper behaviour focusing on building alliance and giving emotional support to the help-seeker (client or child-centred counsellor behaviour, CCCB) (Burleson, & Goldsmith,1998;Cutrona, 1990;Cutrona & Suhr, 1992;Horowitz et al, 2001;Jones & Burleson, 1997;Mishara et al, 2007) also in the context of child helplines (Fukkink, 2011;van Dolen & Weinberg, 2017;Williams, Bambling, King, & Abbott, 2009). The concept of support matching assumes that people dealing with different types of problems (stressors) may benefit from different types of support (Cutrona, 1990;Cutrona & Russell, 1990;Green-Hamann & Sherblom, 2014;Horowitz et al, 2001;Loane & D'Alessandro, 2013;Rains et al, 2015;Rains, Brunner, Akers, Pavlich, & Goktas, 2017;van Dolen & Weinberg, 2017). The theory of Lazarus and Folkman (1984) predicts that an emotion-focused coping approach (also referred to here under CCCB) is more effective in cases of uncontrollable events, whereas individuals impacted by controllable events might benefit more from a problem-centred approach (also referred to here as PCCB), providing instrumental support in the form of information and advice (Cutrona, 1990;van Dolen & Weinberg, 2017).…”
Section: Social Support In Counsellingmentioning
confidence: 99%
“…Whilst in the nineties some studies identified several negative effects of online communication, such as the addictive use, casual relationships with strangers and cyberbullying, current studies have highlighted, rather than risks, certain benefits (Ahn, 2011;Rains, Brunner, Akers, Pavlich, & Goktas, 2016). A recent review described several benefits of online communication, such as an increase in self-esteem, perceived social support and social capital, more confidence in identity experimentation and more revelation opportunities (Valkenburg & Peter, 2009).…”
Section: Introductionmentioning
confidence: 99%